2010
DOI: 10.1258/acb.2009.009018
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the potential association of vitamin D binding protein with lipoproteins

Abstract: Background: Vitamin D binding protein (DBP) acts as a vitamin D carrier and an actin scavenger. We have previously reported a correlation between serum DBP and lipid parameters in a cystic fibrosis population. In the present study, the relationship between serum DBP, lipoprotein fractions and vitamin D is investigated. Methods: The presence of DBP in lipoprotein fractions was examined using precipitation, gel permeation chromatography and ultracentrifugation. The association between DBP and lipids was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Elevated levels of VDP in plasma/serum/CSF have previously been reported in several neuropsychiatric disorders, such as schizophrenia, multiple sclerosis and Guillain-Barre syndrome (d'Aguanno et al 2010 ;Rithidech et al 2009 ;Wan et al 2007). Apart from its role in transporting vitamin D metabolites, VDP also exhibits several other functions including actin scavenging, fatty acid transport and modulation of immune and inflammatory responses (Gomme & Bertolini, 2004 ;Speeckaert et al 2006Speeckaert et al , 2010White & Cooke, 2000). An elevated VDP level may be associated with abnormalities in immunoregulation and the lipid profile found in MDD.…”
Section: Discussionmentioning
confidence: 96%
“…Elevated levels of VDP in plasma/serum/CSF have previously been reported in several neuropsychiatric disorders, such as schizophrenia, multiple sclerosis and Guillain-Barre syndrome (d'Aguanno et al 2010 ;Rithidech et al 2009 ;Wan et al 2007). Apart from its role in transporting vitamin D metabolites, VDP also exhibits several other functions including actin scavenging, fatty acid transport and modulation of immune and inflammatory responses (Gomme & Bertolini, 2004 ;Speeckaert et al 2006Speeckaert et al , 2010White & Cooke, 2000). An elevated VDP level may be associated with abnormalities in immunoregulation and the lipid profile found in MDD.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, with regard to the biochemical components of metabolic syndrome, it is suggested that the protein may be a protective agent against their occurrence. In the analysis of Speeckaert et al ., negative correlations between the VDBP concentration and the fraction of LDL lipoproteins, as well as triglyceridemia, were observed [36]. In addition, it is thought that VDBP, by regulating the amount of active vitamin D in β-cells of the pancreas, may affect insulin secretion, and thus affect the prevalence of insulin resistance and type-2 diabetes mellitus [11].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C could also promote LDL receptor activity [39] or modulate cholesterol ester transfer protein activity. The positive association between VLDL concentration and vitamin D intake could be explained by the fact that vitamin D binding protein and 25(OH)-vitamin D(3) are present in VLDL [40]. More VLDL would mean more vitamin D binding protein circulating within these lipoprotein particles and therefore would increase the amount of vitamin D associated.…”
Section: Discussionmentioning
confidence: 99%